Ultrasound-Guided Interscalene Brachial Plexus Block for Pathological Humerus Fracture due to Multiple Myeloma with Systemic Manifestation: Useful Option for Management in Low-Income Countries. (17th October 2020) - Hamal, Pawan Kumar; Lamichhane, Bibena; Pokhrel, Nabin; Singh, Janith; Yadav, Rupesh Kumar
Abstract : Anesthetic management of pathological fracture due to multiple myeloma with systemic manifestation poses a perioperative challenge especially in low-resource setups like Nepal. Regional anesthesia using ultrasound-guided block can improve the accuracy, reduce complications, and improve overall perioperative management of pathological fractures due to malignancy with systemic spread in resource-deprived setups. We present a case of a 53-year-old lady with pathological fracture of left humerus shaft, a diagnosed case of multiple myeloma with compression fracture of multiple lumbar spine with chest wall metastasis with resolving acute kidney injury with chest infections. Ultrasound-guided interscalene brachial plexus block with sedation was done for open reduction internal fixation of humerus shaft fracture taking in consideration the overall high perioperative risk of patient. Intraoperative hemodynamic was uneventful, with no neurological sequelae and good recovery status perioperatively. Ultrasound-guided interscalene brachial plexus block if done cautiously can be a very useful alternative technique for better perioperative outcome in patients with malignancy with systemic spread in areas where expertise is scarce and resource is limited.